Efektifitas Penyuluhan Kesehatan Tentang Menarche Terhadap Pengetahuan Siswi - Astri Wahyuningsih; Sri Wahyuni; Linda Adi Anggraini (INVOLUSI: Jurnal Ilmu Kebidanan, 2023)
Background: Menarche is a term for menstruation which occurs for the first time between the ages of 9 – 16 years. Objective: To determine the effectiveness of health counseling about menarche on female students' knowledge. Method : The method of this research is a quasi-experimental design by forming a one group pretest posttest design. The population in this study were 32 female students. Sampling using total sampling, namely by taking all members of the population as respondents. The number of samples in this study were 32 female students. The instrument used in this research is a questionnaire. Results: The results in this study were that the majority of respondents had a good level of knowledge as many as 2 people at the pretest stage and the majority of respondents had a good level of knowledge as many as 22 people at the posttest stage. Data analysis using the Wilcoxon test. The results of bivariate analysis with the Wilcoxon test obtained a p value of 0.000 (p <0.05). Conclusion: The conclusion of this study is that there is a significant comparison between pretest and posttest scores in increasing female students' knowledge about menarche. Suggestion: The school should be able to conduct reproductive health education about menarche which supports readiness for menarche.